CD5L, Macrophage Apoptosis Inhibitor, Was Identified in Epicardial Fat-Secretome and Regulated by Isoproterenol From Patients With Heart Failure - Agra-Bermejo, Rosa M.; Cacho-Antonio, Carla; Rozados-Luis, Adriana; Couselo-Seijas, Marinela; Fernandez, Angel L.; Martinez-Cereijo, J. M.; Bravo, S. B.; Gonzalez-Juanatey, Jose R.; Eiras, Sonia (Frontiers in Physiology, 2020)
Objectives: Neurohormonal dysfunction, which can regulate epicardial fat activity, is one of the main promoters of atrial fibrillation (AF) in patients with heart failure (HF). Our aim was to study the epicardial fat mediators for AF in patients with HF and its catecholaminergic regulation. Methods: We have included 29 patients with HF who underwent cardiac surgery and followed up for 5 years. Released proteins by epicardial adipose tissue (EAT) after isoproterenol treatment were identified by nano-high performance liquid chromatography (HPLC) and triple time of flying (TOF) analysis. Common and differential identified proteins regarding groups of patients with AF before and after surgery were determined by Fun Rich tool. Plasma and epicardial fat biopsies-proteins were quantified by western blot. Results: Our results identified 17 common released proteins by EAT, after isoproterenol treatment, from HF patients who suffered AF or developed new onset AF during follow-up. Mostly, they were involved on inflammatory response and extracellular matrix. One of them was CDL5, macrophage apoptosis inhibitor. Its secretion by isoproterenol treatment was validated on western blot. The CD5L levels on epicardial fat were also higher in the group of male patients who present or develop AF (0,44±0,05 vs. 0,18±0,15; p<0,016). However, there was not differences regarding plasma levels. Conclusions: Our results suggest the role of epicardial fat-CD5L as mediator of AF and its posible paracrine effect by catecholaminergic activity.